2022
DOI: 10.1063/5.0071606
|View full text |Cite|
|
Sign up to set email alerts
|

Measurement of plasma flow and electron energy probability function in radio frequency plasma thruster with a magnetic cusp

Abstract: The use of a cusp magnetic field is studied to improve the thrust performance of small electrodeless radio frequency (RF) plasma thrusters based on a theoretical analysis of a magnetized inductively coupled plasma. In this type of thruster, electrons play a critical role in determining the thrust performance. The electron energy probability function (EEPF) and two-dimensional profiles of the plasma parameters in the cusp-type magnetic field RF thruster are investigated to characterize the plasma flow. Non-Maxw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…During the plasma expansion in the MN, an internal azimuthal plasma current spontaneously develops due to the diamagnetic nature; the axial Lorentz force arising from the diamagnetic current and the radial magnetic field increases the thrust, as predicted and demonstrated by theories and experiments [18][19][20][21] . The conversion efficiencies from the rf power to the thrust energy were about 0.5-5% in early experiments [22][23][24][25][26] and approaches about 20% in recent years 27 , based on the scientific insights into the thrust generation processes. Some models and experiments have identified that the energy and momentum losses to the source wall yield the low thruster efficiency and the inhibition of the loss by increasing the strength of the axial magnetic fields have been discussed and demonstrated so far 28,29 .…”
mentioning
confidence: 99%
“…During the plasma expansion in the MN, an internal azimuthal plasma current spontaneously develops due to the diamagnetic nature; the axial Lorentz force arising from the diamagnetic current and the radial magnetic field increases the thrust, as predicted and demonstrated by theories and experiments [18][19][20][21] . The conversion efficiencies from the rf power to the thrust energy were about 0.5-5% in early experiments [22][23][24][25][26] and approaches about 20% in recent years 27 , based on the scientific insights into the thrust generation processes. Some models and experiments have identified that the energy and momentum losses to the source wall yield the low thruster efficiency and the inhibition of the loss by increasing the strength of the axial magnetic fields have been discussed and demonstrated so far 28,29 .…”
mentioning
confidence: 99%